Superficial thermal response to CrossFit® workout - Eduardo Borba Neves; Eduardo Camillo Martinez; Franciele De Meneck; Victor Machado Reis (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aims: Recently, high-intensity training methods have become popular, integrating the cardiovascular and neuromuscular training in a single training session, among these methods is CrossFit®. The objective of this study was to analyze the superficial thermal response to CrossFit® exercise in men and women, in order to use this knowledge to prevent overuse injuries. Methods: Nineteen volunteers involved in CrossFit® exercise for more than 6-month (12 males and 7 females) were recruited. The acquisition of the thermal images was performed in a climatized room in two moments, at rest (before exercise), and after one CrossFit® training session. The training session lasted 45min, comprising warm-up (10-min), accessory work (15-20min), and workout of the day (15-20-min). Before the first image acquisition, volunteers were acclimated for 15 min. The Wilcoxon signed-rank test was used to compare the skin temperature between pre- and post-exercise. Results: Temperatures rose significantly pre- to post-exercise in the forearm and anterior thigh regions, while it decreased in the anterior thorax and dorsal lower back regions. These results were found both, in the overall sample, and the male volunteers, but not when the female results were isolated. Conclusion: It can be concluded that superficial thermal response to one CrossFit® training session was characterized and was different for men and women. The superficial thermal responses were aligned with the physiological alterations promoted by other modalities, such as resistance training, cycling, and running.